2022
DOI: 10.3390/biomedicines10051031
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan Ameliorates Cardiopulmonary Function but Not Inflammatory Response in a Dual Model of Experimental ARDS

Abstract: The calcium sensitiser levosimendan, which is used as an inodilator to treat decompensated heart failure, may also exhibit anti-inflammatory properties. We examined whether treatment with levosimendan improves cardiopulmonary function and is substantially beneficial to the inflammatory response in acute respiratory response syndrome (ARDS). Levosimendan was administered intravenously in a new experimental porcine model of ARDS. For comparison, we used milrinone, another well-known inotropic agent. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Following approval of the state and institutional animal care committee (Landesuntersuchungsamt Rheinland-Pfalz, Koblenz, Germany; G16-1-015, G18-1-044, G20-1–135) eight male pigs ( Sus scrofa domesticus; weight 30 ± 2 kg, aged 8 to 12 weeks) were prospectively examined in the vehicle group in the past 2 years for one of the two used animal models and post-hoc compared in this study (G16-1-015 = 8 vehicle animals, ARDS induced with LPS; G18-1-044/G20-1-135 = 4 vehicle animals from each study, ARDS induced with the double-hit model). The results from one of the previous mentioned studies (G18-1-044) have already been published [ 8 ]. All the cited studies were prospectively performed in compliance with the ARRIVE guidelines [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following approval of the state and institutional animal care committee (Landesuntersuchungsamt Rheinland-Pfalz, Koblenz, Germany; G16-1-015, G18-1-044, G20-1–135) eight male pigs ( Sus scrofa domesticus; weight 30 ± 2 kg, aged 8 to 12 weeks) were prospectively examined in the vehicle group in the past 2 years for one of the two used animal models and post-hoc compared in this study (G16-1-015 = 8 vehicle animals, ARDS induced with LPS; G18-1-044/G20-1-135 = 4 vehicle animals from each study, ARDS induced with the double-hit model). The results from one of the previous mentioned studies (G18-1-044) have already been published [ 8 ]. All the cited studies were prospectively performed in compliance with the ARRIVE guidelines [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies [42,43] have suggested that levosimendan has an anti-inflammatory response that limits the production of chemokines and inflammatory cytokines. The anti-inflammatory effect prevents the activation and recruitment of immune cells during sepsis.…”
Section: E617mentioning
confidence: 99%